1987
DOI: 10.1172/jci113185
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of nicotinamide adenine dinucleotide- and nicotinamide adenine dinucleotide phosphate-linked 15-hydroxyprostaglandin dehydrogenases in placentas from normotensive and preeclamptic/eclamptic pregnancies.

Abstract: Concentrations of prostaglandins E2 and I2 may be decreased in preeclamptic and eclamptic pregnancies. Because these prostaglandins produce vasodilation and inhibit platelet aggregation it has been suggested that a reduction in their biosynthesis might play an important role in the pathogenesis of the hypertension and coagulation abnormalities associated with preeclampsia. Placental tissue is an extremely rich source of several enzymes that catalyze the catabolism of prostaglandins. The present study was initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…One study has found a twofold reduction of PGDH mRNA levels in placental tissue of patients with pre-eclampsia, compared with matched controls [ 24 ]. Others have found an increase in the activity of PGHD in pre-eclamptic placentas [ 25 ]. We found an upregulation (1.48-fold) of PGDH in the pre-eclamptic placentas.…”
Section: Discussionmentioning
confidence: 99%
“…One study has found a twofold reduction of PGDH mRNA levels in placental tissue of patients with pre-eclampsia, compared with matched controls [ 24 ]. Others have found an increase in the activity of PGHD in pre-eclamptic placentas [ 25 ]. We found an upregulation (1.48-fold) of PGDH in the pre-eclamptic placentas.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalance of the vasoconstrictive and vasodilatory prostanoids has been reported to be associated with the pathophysiology of hypertensive pregnancy, possibly due to deficiency of formation or increased metabolism of vasodilatory prostaglandins (Jarabak et al 1987), or increased production of thromboxane A, (TXA,) (Walsh 1985). The TXA,/prostacyclin (PGI,) ratio is increased in maternal and umbilical venous plasma (Yamaguchi & Mori 1985), in amniotic fluid (Ylikorkala et al 1981) and in placenta (Walsh 1985).…”
mentioning
confidence: 99%